Prevalence of lumbosacral transition vertebrae in symptomatic adults and the levels of degeneration in the suprajacent disc - Song, Joshua (2024)
Lumbosacral transition vertebra (LSTV) is a common occurrence and its prevalence ranges from 2.6% to 35.6%. Our aim is to study this phenomenon in the adult Singaporean population and assess the level of degeneration of the suprajacent disc in those with LSTV. Retrospectively, 545 patients (Age = 57.6 ± 18.3 years; Male = 277; Female = 268) who underwent radiographic evaluation of the lumbar spine for lower back pain or radicular symptoms were shortlisted. LSTV was found to be present in 106 patients (19.4%) with sacralization of L5 and lumbarization of S1 occurring in 96 patients (17.6%) and 10 patients (1.8%), respectively. The most common form of LSTV was Castellvi type IIA (46 patients; 43.4%). Based on Pfirrmann grading, Grade IV disc degeneration was most common in both the LSTV level (63%) and the unfused suprajacent level (77%) in those with LSTV. There was a significantly higher number of patients with grade IV and above degeneration in the suprajacent disc level among those with LSTV when compared to the last unfused (L5-S1) disc level in those without LSTV (84% vs. 65%; p = 0.0001). This suprajacent disc degeneration seen in patients with LSTV may contribute to low back pain and related problems in these patients.